A systematic review and meta-analysis of the COVID-19 associated liver injury (2020)
Introduction and Objectives: The novel coronavirus disease 2019 (COVID-19) has affected more than 5 million people globally. Data on the prevalence and degree of COVID-19 associated liver injury among patients with COVID-19 remain limited. We conducted a systematic review and meta-analysis to assess the prevalence and degree of liver injury between patients with severe and non-severe COVID-19. Methods: We performed a systematic search of three electronic databases (PubMed/MEDLINE, EMBASE and Cochrane Library), from inception to 24th April 2020. We included all adult human studies (>20 subjects) regardless of language, region or publication date or status. We assessed the pooled odds ratio (OR), mean difference (MD) and 95% confidence interval (95%CI) using the random-effects model. Results: Among 1543 citations,there were 24 studies (5961 subjects) which fulfilled our inclusion criteria. The pooled odds ratio for elevated ALT (OR = 2.5, 95%CI: 1.6-3.7, I 2 = 57%), AST (OR = 3.4, 95%CI: 2.3-5.0, I 2 = 56%), hyperbilirubinemia (OR = 1.7, 95%CI: 1.2-2.5, I 2 = 0%) and hypoalbuminemia (OR = 7.1, 95%CI: 2.1-24.1, I 2 = 71%) were higher subjects in critical COVID-19. Conclusion: COVID-19 associated liver injury is more common in severe COVID-19 than non-severe COVID-19. Physicians should be aware of possible progression to severe disease in subjects with COVID19-associated liver injury